PRODUKTIVITAS ALAT TANGKAP PANCING ULUR (HAND LINE) PADA RUMPON PORTABLE DI PERAIRAN ACEH UTARA - Imam Shadiqin; Roza Yusfiandayani; Mohammad Imron (Jurnal Teknologi Perikanan dan Kelautan, 2018)
The rumpon portable is a fishing auxiliary device that functions to collect fish with 11,000-15,000 Hz frequencey by using sound on the atractors of portable FADs that be able to collect small pelagic fish around portable FADs. The small pelagic fish have habit to configurate a schooling group in their lives for migrating, feeding, and spawning. The hand line is one of fishing gear used by small-scale fisherman to catch small pelagic fish. Therefore, it is important to know about productivity of handline on the portable FADs. This study used production data of handline with 15 fishing trips in August-September 2018 located in the waters of North Aceh. The result showed that 8 types,that is selar tetengkek (Megalaspis cordyla), pompano (Caranx ignobilis), grauper (Epinephelus fuscoguttatus), selar (Selaroides leptolepis), squid (Loligo indica), turmeric (Upeneus moluccensis), barred (Scomberomorini), and mackerel (Rastrelliger) with a total weight of 24,25 kg was caught around portable FADs using handline. The average productivity of handline on the portable FADs was 1,61 kg/trip. The catch composition showed that the dominant catch was squid.